MODEL IMPLEMENTASI KEBIJAKAN PENDIDIKAN KOTA SEMARANG PADA ERA OTONOMI DAERAH - PPs Universitas Negeri Semarang, Muhdi (Jurnal Manajemen Pendidikan, 2012)
Abstract. Local autonomy in the education sector has been implemented for more than ten years; however, the results have not been satisfactory yet and have even created various problems, including in Semarang City. The objective of this research is to obtain the implementation model of the educational policy of Semarang City in the local autonomy era. This research uses the research and development approach. The research results show that the appropriate implementation model of the educational policy of Semarang City in the local autonomy era is the one which applies the interactive and participative principles, management functions and good governance. The decision making and the accomplishment of the educational policy should be done through the interactions among the decision makers, the decision implementers and the decision users so that all parties can give inputs and evaluation. The implementation of the policy is accomplished by applying the management functions especially organizing, actuating and controlling as well as applying the principle of good governance, i.e. transparency, accountability, fairness and responsiveness.Abstrak. Otonomi daerah bidang pendidikan telah lebih sepuluh tahun dilaksanakan; namun hasilnya belum menggembirakan, bahkan memunculkan berbagai masalah baru, termasuk di kota Semarang. Tujuan penelitian ini adalah mendapatkan model implementasi kebijakan pendidikan kota Semarang pada era otonomi daerah. Pendekatan dalam penelitian ini adalah penelitian dan pengembangan. Hasil penelitian ini adalah: bahwa model implementasi kebijakan pendidikan kota Semarang pada era otonomi daerah yang sesuai adalah model implementasi kebijakan pendidikan yang menerapkan prinsip interaktif, partisipatif, fungsi manajemen dan good governance. Penetapan kebijakan pelaksana dilakukan dengan interaksi antara penentu kebijakan, pelaksana kebijakan dan pengguna kebijakan, sehingga para pihak dapat memberikan masukan dan evaluasi. Pelaksanaan kebijakan dilakukan dengan menerapkan fungsi manajemen khususnya organizing, actuating, controlling, dan menerapkan prinsip good goverenance yaitu transparansi, akuntabilitas, fairnes dan responsivitas.Key words: Interactive, participative, management, good goverenance.